2008
DOI: 10.1016/j.socscimed.2007.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use in sub-Sahara Africa: Estimates from the demographic health surveys

Abstract: Despite the growing problem of global tobacco use, accurate information on the prevalence and patterns in the world's poorest nations remains sparse. For sub-Sahara Africa, in particular, a weak knowledge base limits the targeting of strategies to combat the potential growth of tobacco use and its harmful effect on future mortality. To describe the prevalence and social patterns of the use of cigarettes and other tobacco in Africa, this study examines population-based data from 16 Demographic Health Surveys (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
123
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(179 citation statements)
references
References 18 publications
41
123
10
Order By: Relevance
“…Ghana has been reported to have the lowest rate of tobacco use in Africa. 38 More than half (64.4%) of the smokers in this study were low-rate smokers (consuming fewer than five cigarettes per day). Smoking initiation of tobacco use in this study was 18.3 ± 5.1 years and 22.6 ± 8.0 years for male and female, respectively.…”
Section: Discussionmentioning
confidence: 70%
“…Ghana has been reported to have the lowest rate of tobacco use in Africa. 38 More than half (64.4%) of the smokers in this study were low-rate smokers (consuming fewer than five cigarettes per day). Smoking initiation of tobacco use in this study was 18.3 ± 5.1 years and 22.6 ± 8.0 years for male and female, respectively.…”
Section: Discussionmentioning
confidence: 70%
“…However, some of these laws are weak, with allowances low-income countries. Work in Asia and Africa generally shows that higher SEP is associated with less current smoking (Hoang, Byass, Dao, Nguyen, and Wall, 2007;Pampel, 2008;Pappas, Akhtar, Gergen, Hadden, and Khan, 2001), except in rural areas in Pakistan and India where there was no socioeconomic patterning (Pappas et al;Singh et al, 1997). In Latin America, a study of adults 60 years and older in seven cities in Latin America and the Caribbean in 1999-2000 reported that higher education was associated with less current smoking for men and showed no gradient for women (Kim et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The Framework Convention on Tobacco Control legislates protection from tobacco smoke exposure; the packaging and labeling of tobacco products; and the advertising, promotion, and sponsorship of tobacco products. Pampel 27 examined data on tobacco use among men (age, 15-54 years) and women (age, 15-49 years) from 16 demographic health surveys in 14 Sub-Saharan countries. According to Pampel's analysis, the gradation of the prevalence of cigarette smoking increases from among West-Central African men (lowest use) to southern African men (medium use) and then to men from Madagascar and East-Central Africa (highest use).…”
Section: Africa Cross-country Associations Of Cvds and Risk Factors Imentioning
confidence: 99%